Analysis of Mechanical and Acoustic Emission Characteristics of Rock Materials with Double-Hole Defects Based on Particle Flow Code - Qi Zhang; Xiao Wang; Long-gang Tian; Dong-mei Huang (Shock and Vibration)
There are a lot of fissures, holes, and other defects in the formation of natural rocks. Under the influence of the external loads, these defects may cause engineering problems. Therefore, it is of great significance to analyze the characteristics of damage evolution of the defective rocks. In the study, the double-hole defective rocks with different angles of the center connection line are considered and the numerical models are established firstly. Then the mechanical behavior and acoustic emission (AE) characteristics are analyzed systematically. Finally the laws of damage evolution of the defective rock materials are investigated based on the AE characteristics. The research results show that the stress-strain behavior of the defective rocks can be divided into elastic stage, plastic stage and failure stages. The characteristics of acoustic emission evolution and laws of damage evolution are closely related to the stress-strain relationship. The elastic modulus of the double-hole defective rocks is similar with different angles of the center connection line, but the peak strength is different. The shape of the peak strength of these defective rocks is a W type owing to the different failure modes. The influences of different angles of the center connection line on the characteristics of AE evolution include the maximum events number, the strain value of the initial AE events and the maximum AE events, and the strain range of the serious AE events. Different angles of the center connection line have different influences on the laws of damage evolution of the double-hole defective rocks.